Nuclear-Powered Submarines and the Global Nuclear Order (Global Journal of Human-Social Science, 2024)
The nuclear propulsion of submarines has never been raised as a source of controversy since the countries operating nuclear-powered submarines are only the five Nuclear-Weapon States recognized in the NPT plus India which is not a signatory to the NPT However with the advancement of the Brazilian nuclear-powered submarine program and the announcement that Australia will operate and develop nuclear-powered submarines this issue has become a hot spot on the non-proliferation agenda In this context two questions arise What are the perceptions of the main actors involved with the issue of nuclear energy use for the propulsion of submarines of Non-nuclear Weapon States What are the impacts of these perceptions on the global nuclear order This article argues that a new normative inequality would be in the formation process in which there would be the have and have-not users of nuclear energy for the propulsion of submarines
Keywords: global nuclear order non-proliferation nuclear-powered submarines